BASIC ELEMENTS OF THE MECHANISM OF MANAGEMENT OF THE INTELLECTUAL CAPITAL - A. Zinchenko; L. Mikhailova; A. Sazonov (Вестник университета)
The modified multicomponent organizational and economic mechanism of management of the intellectual capital has considered. This is the technical system necessary for achievement of the goals, the organization sets, using symbiotic connection of the valid economic model and the intellectual capital. The mechanism is based on the building an optimal objective function to achieve the goals of the company. The implementation of that mechanism in practice will substantially allow innovation-active organizations to improve the quality of developed and adopted management decisions.